Analisis Hukum Jaminan Pembiayaan Modal Usaha Dalam Akad Mudharabah Pada Perbankan Syariah - Kasmawati Kasmawati; M Rivaldi; Rodhi Agung Saputra (PAMALI: Pattimura Magister Law Review, 2022)
Introduction: The settlement of the mudharabah contract guarantee dispute can have two alternative settlements, namely the religious court and the arbitration body, while the absolute execution of the decision is carried out through the religious court in accordance with Article 49 of Law Number 3 of 2006 concerning Religious Courts.Purposes of the Research:  Examine the mudharabah contract guarantee, which has been regulated in the Fatwa of the National Syari'ah Council Number 07/DSN-MUI/IV/2000 concerning Mudharabah Financing.Methods of the Research: The research method used is a normative research method with a statute approach and analyzed using content analysis.Results of the Research: The findings of this study indicate that the regulation regarding the settlement of collateral disputes in Mudharabah contracts in Islamic banking is regulated in Article 55 of Law Number 21 of 2008 concerning Islamic Banking and the execution of guarantees can only be implemented when the principles of execution have been fulfilled.